2020
DOI: 10.1038/s41467-020-15642-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the heterogeneity of macromolecular machines by mass photometry

Abstract: Sample purity is central to in vitro studies of protein function and regulation, and to the efficiency and success of structural studies using techniques such as x-ray crystallography and cryo-electron microscopy (cryo-EM). Here, we show that mass photometry (MP) can accurately characterize the heterogeneity of a sample using minimal material with high resolution within a matter of minutes. To benchmark our approach, we use negative stain electron microscopy (nsEM), a popular method for EM sample screening. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 183 publications
(177 citation statements)
references
References 43 publications
7
154
0
Order By: Relevance
“…MP reveals true equilibrium distributions, reports on populations rather than ensembles due to its single-molecule nature and requires minimal sample volumes (mL) and concentrations (<<mM). Moreover, MP naturally extends toward characterizing structural heterogeneity 9 and protein-protein interactions, 10 resulting in a universal platform for studying biomolecules.…”
Section: The Bigger Picturementioning
confidence: 99%
“…MP reveals true equilibrium distributions, reports on populations rather than ensembles due to its single-molecule nature and requires minimal sample volumes (mL) and concentrations (<<mM). Moreover, MP naturally extends toward characterizing structural heterogeneity 9 and protein-protein interactions, 10 resulting in a universal platform for studying biomolecules.…”
Section: The Bigger Picturementioning
confidence: 99%
“…We next investigated the oligomeric state of DDX21 in the presence of RNA. The protein-RNA complexes were unstable under the conditions suitable for SEC-MALS analysis; therefore we used mass photometry to estimate the molecular mass of the macromolecular assemblies in solution (Sonn-Segev et al, 2020). The basis of mass photometry is the optical detection of the scattering signal generated by a single particle at the glass-water interface.…”
Section: Ddx21 Binds R-loops As a Dimermentioning
confidence: 99%
“…The precise stoichiometry and oligomerization state of the LUBAC complex have not been established although recent structural work has suggested a 1:1:1 stoichiometry between the three core components (Fujita et al, 2018). To determine the stoichiometry and oligomerization state of the LUBAC complex we used mass photometry (MP), a technique that enables accurate mass measurements based on the scattering of light by single macromolecules in solution (Sonn-Segev et al, 2019, Young et al, 2018 ( Figure 2D and Figure EV4). MP measurements showed that the majority of species present in the samples had average masses of 231 kDa (Peak II), and 454 kDa (Peak III) (EV Table 1).…”
Section: The Lubac Complex Exists As Monomers and Dimers With A 1:1:1mentioning
confidence: 99%